Kajian resiko usaha pengeringan ikan teri di Desa Terapung Kecamatan Mawasangka Kabupten Buton Tengah Sulawesi Tenggara - Mustiharian, Dewi; Yusuf, Sarini; Riani, Irdam; Risfandi; Piliana, Wa Ode (Jurnal Sosial Ekonomi Perikanan, 2024)
Fish is one of fishery commodity that very susceptible to spoiled, hence needs to be preserved. The easiest and low cost preservation technique is drying method that is commonly practiced by remote coastal communities where is no cold storage facilities provided. This study aims to asses the risk that may occurred at anchovy dried processing plants at Terapung Village of Mawasangka Central Buton Regency South East Sulawesi April 2021. The research samples included nine anchovy dried produsen which data was collected using sensus method as population in this study. In the other hand data of production inputs and marketing price were obtained through structured questionnaires. The average income of anchovy drying plants was IDR. 33,079,470,-/week. Average delivery of 7,920 kg/week with a price of IDR. 120,000,-/kg for super dried anchovies and IDR. 100,000,-/kg for jumbo dried anchovies. The variationcoefficient of anchovy drying plants was 0.11 ≤ 0.5 with a lower limit of income (L) of IDR. 25,964,940,-/week (L≥ 0). The result of study showed that the drying plants of anchovies in the Terapung Village of Mawasangka District Central Buton Regency will obtain benefit at every one production period. Therefore, sustainable harvest of anchovies is a must be ensure income suitability of dried anchovy’s processing plants.